Efforts to Improve Children's Motor Skills and Creativity Through Activities at The Center for Natural Materials - Rahmah Rahmah; Zainal Abidin; Ibdalsyah Ibdalsyah (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
This classroom action research aims to improve children's motor and creativity skills through activities in the natural materials center at TK Kesuma Bangsa, Sukabumi. The research was conducted in three cycles, each consisting of two meetings and involving 14 children in group A. Data collection methods included observation and documentation. In the pre-cycle stage, both motor and creativity skills were still in the "emerging" category, with average scores of 30.6% and 29.1%, respectively. Improvements were observed in each cycle: by Cycle II, average motor skills reached 66%, and creativity reached 65.8%. In Cycle III, both aspects exceeded the success criteria of 90%, with motor skills reaching 92.4% and creativity 90.5%. These results indicate that natural materials-based learning activities effectively enhance children's motor and creative abilities when supported by varied media, appropriate settings, and teacher facilitation.